HUBUNGAN ANTARA MEKANISME KOPING TERHADAP STRES DENGAN KEJADIAN HIPERTENSI PADA WARGA DI DESA NGELOM SROYO JATEN KARANGANYAR - Dinar Ariasti; Thia Nur Pratiwi (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
Background: Based on preliminary observations of researchers in Ngelom SroyoJaten Karanganyar village, some people who have a disease due to hypertensionor problem-solving coping mechanism against stress effectively so that stress isincreasing and causing hypertension.The purpose of this study was to determine the relationship between copingmechanisms against stress with hypertension in residents in the village NgelomSroyo Jaten Karanganyar.The subjects were residents of the village of Karanganyar Jaten Ngelom Sroyototaling 40 residents. Sampling was done by purposive samplingMethods in this study is analytical research design correlation to determine therelationship between coping mechanisms against stress with hypertension inresidents in the village Ngelom Sroyo Jaten Karanganyar. The collected datawere then analyzed with the chi square test with p = 0.05.The results of the study there were 13 respondents to the mechanism of copingwith stress effectively have hypertension, 3 respondents to the mechanism ofcoping with stress effectively does not have hypertension, 17 respondents with acoping mechanism to stress ineffective hypertension and 7 respondents with acoping mechanism to stress ineffective does not have hypertension, the resultobtained p equal to 0.004 so that the value of P <0.05, which means that Horefused and Ha accepted.The conclusion of this study there is a relationship between coping mechanismsagainst stress with hypertension in residents in the village Ngelom Sroyo JatenKaranganyar.Keywords: coping mechanism to stress, hypertension